2022
DOI: 10.1007/s11224-022-01932-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceiving SARS-CoV-2 Mpro and PLpro dual inhibitors from pool of recognized antiviral compounds of endophytic microbes: an in silico simulation study

Abstract: Coronavirus disease 2019 (COVID-19) persists and shook the global population where the endgame to this pandemic is brought on by developing vaccines in record-breaking time. Nevertheless, these vaccines are far from perfect where their efficiency ranges from 65 to 90%; therefore, vaccines are not the one only solution to overcome this situation, and apart from administration of vaccines, the scientific community is at quest for finding alternative solutions to incumber SARS-CoV-2 infection. In this study, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Apart from the global similarities among the RMSF profiles of the complexes, it is important to focus on the ligand RMSF because it would be desirable to select compounds with low values of this parameter [ 90 ]. The ligand RMSF values for the PLpro complexes were as follows (in descending order): 89–07 (2.58 Å) , 89–32 (1.82 Å) , 89–38 (1.76 Å) , 89–00 (1.65 Å), and GRL0617 (0.97 Å).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from the global similarities among the RMSF profiles of the complexes, it is important to focus on the ligand RMSF because it would be desirable to select compounds with low values of this parameter [ 90 ]. The ligand RMSF values for the PLpro complexes were as follows (in descending order): 89–07 (2.58 Å) , 89–32 (1.82 Å) , 89–38 (1.76 Å) , 89–00 (1.65 Å), and GRL0617 (0.97 Å).…”
Section: Resultsmentioning
confidence: 99%
“…Computational rational drug designing and other computational approaches for developing inhibitors, drugs and alternate medicines have gained lot of attention owing to high accuracy and robustness [ 43 48 ]. Under current study, the top 13 phytochemicals identified using computational screening that showed probable interaction with BChE are curcumin, desmethoxycurcumin, gingerol, asarinin, capsaicin, sesamin, 6-shogaol, rosmarinic acid, piperine, hesperetin, zingiberene, betulinic acid, and ursolic acid.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the absence of Tyr268 in Middle East Respiratory Syndrome (MERS) PLpro caused the lack of activity of known potent inhibitors against this virus (Shin et al, 2020). Notably, Asp164, Tyr264, Tyr268, and Gln269 are among the main key residues identified in the interaction with inhibitors, as reported in recent studies (Prajapati et al, 2022;Sencanski et al, 2022;Shen et al, 2022).…”
Section: Binding Site Profilingmentioning
confidence: 95%